Confidentiality matters! Adolescent males' views of primary care in relation to psychosocial health: a structural equation modelling approach. (2nd October 2022) - Haraldsson, Johanna; Pingel, Ronnie; Nordgren, Lena; Johnsson, Linus; Kristiansson, Per; Tindberg, Ylva
Abstract: Objective: To investigate to what degree adolescent males (1) value confidentiality, (2) experience confidentiality and are comfortable asking sensitive questions when visiting a general practitioner (GP), and (3) whether self-reported symptoms of poor mental health and health-compromising behaviours (HCB) affect these states of matters. Design: Cross-sectional. Setting: School-based census on life, health and primary care in Region Sörmland, Sweden. Subjects: 2, 358 males aged 15–17 years (response rate 84%). Main outcome measures: The impact of poor mental health and HCBs on adolescent males' valuing and experiencing private time with the GP, having professional secrecy explained, and being comfortable asking about the body, love and sex, analysed with structural equation modelling. Results: Almost all respondents valued confidentiality regardless of their mental health or whether they engaged in HCBs: 86% valued spending private time with the GP, and 83% valued receiving a secrecy explanation. Among those who had visited a GP in the past year ( n = 1, 200), 74% had experienced private time and 42% a secrecy explanation. Three-quarters were at least partly comfortable asking sensitive questions. Adolescent males with HCBs were more likely to experience a secrecy explanation (approximative odds ratio [appOR] 1.26; p = 0.005) and to be comfortable asking about sex than their peers (appOR 1.22; p = 0.007). Respondents reporting experienced confidentiality were more comfortable asking sensitive questions (appOR 1.25–1.54; p ≤ 0.010). Conclusion: Confidentiality matters regardless of poor mental health or HCBs and makes adolescent males more comfortable asking sensitive questions. We suggest that GPs consistently offer private time and explain professional secrecy. Key Points: Confidentiality for adolescent males has been scantily studied in relation to mental health and health-compromising behaviours. In this study, most adolescent males valued confidentiality, regardless of their mental health and health-compromising behaviours. Health-compromising behaviours impacted only slightly, and mental health not at all, on experiences of confidentiality in primary care. When provided private time and an explanation of professional secrecy, adolescent males were more comfortable asking the GP sensitive questions.